Analisis Framing Film Vina: Sebelum 7 Hari dalam Media Sosial Tiktok dan X - Adinda Dwi Mulyani; Arfian Suryasuciramdhan; Ine Fitrianingsih; Muadz Alfayeed (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The tragedy of Vina Cirebon, a 16 year old girl who was brutally murdered by eleven people in 2016. The media actually used framing to present the case, which led to the creation of a film entitled